Remanufacturing: A potential sustainable solution for increasing medical equipment availability - Solomon Eze; Winifred Ijomah; T. C. Wong (Journal of Remanufacturing, 2020)
The availability of medical equipment contributes significantly to the stability and sustainability of health care systems. However, in some countries, especially the developing ones, medical equipment availability is a major issue that remains unsolved. Hence, this paper explores the root causes of the issue, reviews existing solution approaches and suggests remanufacturing as a sustainable option. An extensive review was first conducted to uncover key factors contributing to the poor availability of medical equipment in developing countries. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was then used to measure the prominence degrees of the key factors and characterise these factors with an aim to differentiate those that are net drivers from those that are driven. Subsequently, factors that can be addressed by remanufacturing were identified, to determine the potential contribution of remanufacturing in addressing the poor medical equipment availability issue. The result shows that remanufacturing can potentially address at least five of the key factors which account for a cumulative total prominence of 43.5%. Remanufacturing is thus, a viable strategy for improving medical equipment availability in developing countries. In addition to remanufacturing, other recommendations were also proposed to help address the issue.
Keywords: 650; Medical equipment; Remanufacturing; DEMATEL; Medical equipment availability